Persistent Type I Endoleak after Endovascular Treatment with Chimney Technique - Azevedo, Ana Isabel; Braga, Pedro; Rodrigues, Alberto; Ferreira, Nuno; Fonseca, Marlene; Dias, Adelaide; Gama Ribeiro, Vasco (Frontiers in Cardiovascular Medicine, 2016)
Thoracic endovascular aortic repair (TEVAR) is increasingly used in the treatment of acute type B aortic dissection. Type Ia endoleaks are a common complication of the procedure, but its clinical significance as well as the best treatment strategy remain poorly defined. We present a case of a type Ia endoleak following TEVAR in the treatment of acute type B aortic dissection. Chimney technique approach was used in an attempt to seal the endoleak. Although technical success was suboptimal, the patient remained clinically stable and event free. Data regarding the natural course and management of type Ia endoleaks following TEVAR for aortic dissection are sparse. Future research is required to establish the clinical and technical determinants of the need to treat these endoleaks as well as the best treatment strategy.